Balancing the Varied Needs of Master of Music Education Students: Perceptions From Program Directors and Alumni. (April 2021) - Conway, Colleen; Vaughan-Marra, Jessica; Marra, Christopher
The purpose of this study was to examine the perceptions of master of music education degree program directors and alumni from selected schools regarding the ways in which their music education master's programs balance the varied needs of program participants. Findings are presented in the two broad categories of improvement in P–12 teacher learning and preparation for future scholarly work, and the discussion examines the qualitative comparisons between participant responses. Suggestions for graduate programs and future researchers are included.